"Memory is a weapon" : the uses of history and myth in selected post-1960 Kenyan, Nigerian and South African plays - Hutchison, Yvette (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1999.